The Impact of Marriage Harmonization on Gender Equality in Indonesian Society - Masykurotus Syarifah; Muhammad Mujib Karim (The Indonesian Journal of Islamic Law and Civil Law, 2024)
Marriage harmonization is a relevant topic in the social and cultural context of Indonesia. Indonesia, as a country with ethnic, religious, and cultural diversity, is the focus of this study. This research investigates how couples adjust and achieve harmony in their marriages, highlighting key aspects such as effective communication and conflict resolution. It reveals how specific cultural values and norms influence the dynamics of marriage, from gender roles to societal expectations of partners. Findings from this research can have broad social implications, such as offering new insights into supporting healthy relationships in society or informing marriage and family policies. The method used by the author is a qualitative method which pays attention to empirical data with library research.. Through this study, we can understand the strategies couples use to address challenges in their marriages, such as how they handle differences of opinion or tensions in their relationships.